The ideological aspects of reconstructing Warsaw City Centre from the ruins of World War II - Kurcewicz, Urszula (City and War, 2021)
The purpose of this article is to prove that the reconstruction of Warsaw from the devastation brought by World War II was in actuality the construction of a new capital for a socialist state, following Marxist land development principles. The communist authorities considered rebuilding Warsaw City Centre to be of particular importance. Buildings predating the war were seen as symbols of capitalist social relations, which privileged the urban middle class.The author begins by discussing the historically inaccurate appearances upheld by the Polish Workers’ Party, and later by the Polish United Workers’ Party, regarding the extent and causes of the damage sustained by the capital in World War II. The propaganda of the new authorities focused primarily on the destructive activities of the Nazi occupiers, whereas the Soviet bombing and the destruction which ensued during the liberation of Warsaw were either ignored or presented in a dishonest manner.The second part of the article deals with the ideological foundations of rebuilding the City Centre. The communists believed that the capital city should be a relatively compact system organized in the form of multiple architectural compositions forming a cohesive whole. The center of the city was to be socio-political in nature, and its squares and streets were treated as areas for public life. The division into better and worse districts was to be abolished.The final part of the article constitutes an attempt to determine the extent of the autonomy granted to the architects and planners of the Warsaw Reconstruction Office, and to what extent their plans and concepts had to follow the guidelines of party functionaries.